The Effect of Foreign Debt on The Exchange Rate and Its Impact on Monetary Policy in Indonesia - Diah Wahyuningsih; Uun Primangesti Ningsih (MediaTrend, 2019)
The objectives of this study are to analyze the effect of foreign debt on the exchange rate that seen from the foreign debt and the exchange rate, and add the variable of inflationary monetary policy and the interest rate of BI Rate to test its impact on monetary policy in Indonesia. The approach in this study is quantitative approach. Data that used are Time Series data from Asian Development Bank and Indonesian World Bank in 1986-2013. Variables that used are exchange rate, foreign debt, inflation and the interest rate of BI Rate. Method that used in this study is Vector Auto Regression (VAR) analysis. The stages that used in this study testing are stationary test, optimal lag test, Granger causality test, impulse response test, and variance decomposite test in Eviews 6 program. The results of Granger causality test of all variables in this study are unlikely to have a relationship and there are only two variables that give an effect.Based on the results of Granger causality, it shows that there is bidirectional between foreign debt variable that has an effect on the exchange rate in Indonesia and the exchange rate has an effect on the foreign debt in Indonesia. While the foreign debt has an effect on the interest rate of BI Rate. For the results of impulse response test show that the exchange rate variable gives the biggest respond to the shock of foreign debt variable, compared to inflation and the interest rate of BI Rate variables. The results of Variance decomposite show that the contribution which given by foreign debt variable on the exchange rate is relatively bigger compared to the contribution that given by inflation and the interest rate of BI Rate variables.